Longitudinal study of the influence of removable partial denture and chemical control on the levels of Streptococcus mutans in saliva - Rocha, Eduardo Passos [UNESP]; Francisco, S. B.; Del Bel Cury, A. A.; Cury, J. A. (Blackwell Publishing, 2003)
Some studies have evaluated the salivary levels of mutans streptococci (MS) in removable partial denture (RPD) users. Saliva samples (2.0 mL) were obtained from 31 patients in six periods: (T0): immediately before installation of RPD; (T8): 8 days after T0; (T48): 48 days after T0; (T92): 92 days after T0; (T140): 140 days after T0 and (T189): 189 days after T0. The samples were vortexed and serially diluted from 10(-1) to 10(-6) in 0.05 m phosphate buffer (pH 7.4). From each dilution, 0.025 mL was plated on Mitis Salivarius Bacitracin (MSB). The plates were incubated in 5% CO2 at 37 degreesC for 72 h. There was an increase (t -test, P < 0.05) in the number of MS between periods T0 and T48 (mean/s.d., CFU mL(-1) of saliva): T0: 2.26/4.43 x 10(6) and T48: 0.47/1.48 x 10(8) . After this, intensive treatment with CHX was accomplished in 29 patients. Saliva samples were obtained after treatment in four periods: (T24 h): 24 h after T0; (T14): 14 days after T24 h; (T28): 28 days after T24 h, and (T63): 63 days after T24 h. The number of MS in saliva did not decrease (t -test, P > 0.05). A new CHX formulation was applied in 15 patients. Saliva samples were obtained in periods: (T0): before new CHX application; (T24 h): 24 h after T0 and (T82): 82 days after T0. The new CHX reduced MS levels in saliva: (mean/s.d., CFU mL(-1) of saliva): T0: 6.64/8.47 x 10(6) and T24 h: 3.2/4.27 x 10(5) (sign rank, P < 0.05). In conclusion, there was a significant increase in the number of MS in saliva after the installation of RPD. The intensive treatment with a properly formulated CHX was effective in the reduction of MS, between 24 h and 82 days after its application.
Keywords: removable partial denture; saliva; mutans streptococci; chlorhexidine